Karakteristik, Warna, Dan Ukuran Mikroplastik Yang Ditemukan Pada Air Dan Kerang Hijau Di Pulau Pasaran, Lampung - Romaskila, Ulfanida; Widiastuti, Endang Linirin; Susanto, Gregorius Nugroho; Damai, Abdullah Aman; Juliasih, Ni Luh Gede Ratna (Journal of Tropical Marine Science, 2023)
Plastic waste will be degraded into microplastic which has a size of ≤ 5 mm. These microplastic particles change in size and color due to various natural processes that occur in the environment. The purpose of this study was to determine the shape, color and size characteristics of microplastics found around Pasaran Island. Sampling was carried out by taking microplastic samples in water and green mussels around Pasaran Island. Based on the research results, microplastic fragments, films, fibers, granules and foam were found. Microplastic colors consist of black, blue, green, yellow, red, clear, and white. Microplastic fragments, films and fibers were found in the <50µm to 1000 - 5000 µm size group. Granular microplastic types were found in the <50 µm to 100 - 500 µm size group and foam types were found in the <50 µm to 500 - 1000 µm size group.